Ryanodine is a positive modulator of acetylcholine receptor gating in cochlear hair cells - Zorrilla De San Martín, J. (2007)
The efferent synaptic specialization of hair cells includes a near-membrane synaptic cistern, whose presence suggests a role for internal calcium stores in cholinergic inhibition. Calcium release channels from internal stores include 'ryanodine receptors', whose participation is usually demonstrated by sensitivity to the eponymous plant alkaloid, ryanodine. However, use of this and other store-active compounds on hair cells could be confounded by the unusual pharmacology of the α9α10-containing hair cell nicotinic cholinergic receptor (nAChR), which has been shown to be antagonized by a broad spectrum of compounds. Surprisingly, we found that ryanodine, rather than antagonizing, is a positive modulator of the α9α10 nAChR expressed in Xenopus oocytes, the first such compound to be found. The effect of ryanodine was to increase the apparent affinity and efficacy for acetylcholine (ACh). Correspondingly, ACh-evoked currents through the isolated cholinergic receptors of inner hair cells in excised mouse cochleas were approximately doubled by 200 μM ryanodine, a concentration that inhibits gating of the ryanodine receptor itself. This unusual positive modulation was not unique to the mammalian receptor. The response to ACh of chicken 'short' hair cells likewise was enhanced in the presence of 100 μM ryanodine. This facilitatory effect on current through the AChR could enhance brief (∼1 s) activation of associated calcium-dependent K+ (SK) channels in both chicken short hair cells and rat outer hair cells. This novel effect of ryanodine provides new opportunities for the design of compounds that potentiate α9α10- mediated responses and for potential inner ear therapeutics based on this interaction. © 2007 Association for Research in Otolaryngology.